A new hybrid method for demoldability analysis of discrete geometries. (November 2016) - Mercado-Colmenero, Jorge Manuel; Paramio, M.A.R.; Perez-Garcia, Jesus Maria; Martin-Doñate, Cristina
Abstract: In this paper, a new method for demoldability automatic analysis of parts to be manufactured in plastic injection is presented. The algorithm analysis is based on the geometry of the plastic part, which is discretized by a triangular mesh, posing a hybrid discrete demoldability analysis of both the mesh nodes and facets. A first preprocessing phase classifies mesh nodes according to their vertical dimension, assigning each node a plane perpendicular to the given parting direction. By selective projection of facets, closed contours which serve as the basis for calculating the demoldability of the nodes are created. The facets are then cataloged according to demoldability nodes that comprise demoldable, non-demoldable and semi-demoldable facets. Those facets listed as semi-demoldable are fragmented into demoldable and non-demoldable polygonal regions, causing a redefinition of the original mesh as a new virtual geometry. Finally, non-demoldable areas are studied by redirecting the mesh in the direction of the sliding side, and again applying the processing algorithm and cataloging nodes and facets. Resoluble areas of the piece through mobile devices in the mold are obtained. The hybrid analysis model (nodes and facets) takes advantage of working with a discrete model of the plastic part (nodes), supplemented by creating a new virtual geometry (new nodes and facets) that complements the original mesh, providing the designer not only with information about the geometry of the plastic piece but also information on their manufacture, exactly like a CAE tool. The geometry of the part is stored in arrays with information about their manufacture for use in downstream applications. Highlights: The hybrid analysis model takes advantage of working with a discrete model of the part. A new virtual geometry (new nodes and facets) is created complementing the original mesh. The new geometry provides information not only about the geometry but also manufacture. Moldability is performed on any system where no other solid internal information is required.